2010
DOI: 10.1039/b921572g
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast encapsulation in hybrid silica–collagen hydrogels

Abstract: Silica-collagen scaffolds are synthesized by the simultaneous polymerization of aqueous silicates and self-assembly of protein triple helices in the presence of living human dermal fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 33 publications
4
70
0
Order By: Relevance
“…In parallel, the addition of polymers, either natural or synthetic, or of inorganic particles was also studied but most of these works were performed on acellularized systems [11][12][13]. Recently, we have shown that hybrid materials made from collagen and silicates were efficient in decreasing gel contraction and enhancing cell proliferation in the short term [14]. However, in the longer term, reorganization of the collagen network and rapid silica dissolution occurred, to the detriment of cell activity.…”
Section: Introductionmentioning
confidence: 96%
“…In parallel, the addition of polymers, either natural or synthetic, or of inorganic particles was also studied but most of these works were performed on acellularized systems [11][12][13]. Recently, we have shown that hybrid materials made from collagen and silicates were efficient in decreasing gel contraction and enhancing cell proliferation in the short term [14]. However, in the longer term, reorganization of the collagen network and rapid silica dissolution occurred, to the detriment of cell activity.…”
Section: Introductionmentioning
confidence: 96%
“…215,223 Within the scope of bone regeneration, silica-based biohybrid materials involving structural proteins are promising materials for application as implants, according to the good properties of biocompatibility and non-cytotoxicity. 224 An additional advantage of these biohybrids is their bioactivity, a property related to the ability to induce the formation of HAP after soaking in a simulated body fluid (SBF), which is beneficial for the further attachment and proliferation of cells constituting the new tissue. This property has been achieved in different silica-protein hybrids and points out to a possible synergistic effect of silica and collagen on the material bioactivity, since those components alone were not able to promote the formation of apatite.…”
Section: Structural Proteins-based Silica and Silicate Biohybridsmentioning
confidence: 99%
“…There are numerous similar examples including covalent binding of antibodies for functioning of sol-gel films (Fig. 7.7) [135][136][137][138][139][140][141].…”
Section: Biomedical Nanocompositesmentioning
confidence: 97%